What is 4/7 minus 6/3?

Looking for the result of 4/7 - 6/3? Follow this step-by-step guide to understand how to subtract these two fractions.

How to subtract 4/7 by 6/3?

4 7 6 3 = (4 × 3) − (6 × 7) 7 × 3 = -30 21 = -10 7
  1. Multiply the numerator of the first term, with the denominator of the second term: 4 × 3 = 12
  2. Multiply the numerator of the second term, with the denominator of the first term: 6 × 7 = 42
  3. Subtract both of these results together to form the new numerator: 12 − 42 = -30
  4. Multiply both denominators together to form the new denominator: 7 × 3 = 21
  5. Combine the results to get the new fraction: -30/21
  6. Simplify the fraction (-30/21) by dividing both the numerator and the denominator by their GCD (3):
    • -30/3 = -10
    • 21/3 = 7
  7. This gives: -10/7.

The result of subtracting 4/7 and 6/3 is : -10/7 (or -1.4285714285714 in its decimal form)